2023
DOI: 10.1186/s42238-023-00175-y
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Cannabis Legislation: substance use and impaired driving among Canadian rural and urban postsecondary students

Abstract: Background Investigation of cannabis use trends among emerging adults (EA, aged between 18 and 24 years) following 2018 Canadian Recreational Cannabis Legislation (RCL) is critical. EAs report the heaviest cannabis use in Canada and are particularly vulnerable to the onset of problematic substance use. Objectives To describe and compare post-RCL use of cannabis and other state-altering substances, as well as the prevalence of impaired driving, amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Comparing Manitoba and Quebec, both in terms of OLMC/linguistic majority communities and of rural/urban living, OLMC samples in both provinces, especially Quebec’s rural English-speaking OLMC sample, had significantly higher substance use prevalence compared with their linguistic majority peers and national means, 31 consistent with other reports of similar trends for Quebec’s OLMC 35,36 . Conversely, Pocock 16 reported that few addictions-related prevention and treatment services are available in English for Quebec’s rural/remote OLMCs, as is also the case for Francophone OLMCs elsewhere in Canada 26,37 .…”
Section: Results and Key Findingsmentioning
confidence: 93%
See 2 more Smart Citations
“…Comparing Manitoba and Quebec, both in terms of OLMC/linguistic majority communities and of rural/urban living, OLMC samples in both provinces, especially Quebec’s rural English-speaking OLMC sample, had significantly higher substance use prevalence compared with their linguistic majority peers and national means, 31 consistent with other reports of similar trends for Quebec’s OLMC 35,36 . Conversely, Pocock 16 reported that few addictions-related prevention and treatment services are available in English for Quebec’s rural/remote OLMCs, as is also the case for Francophone OLMCs elsewhere in Canada 26,37 .…”
Section: Results and Key Findingsmentioning
confidence: 93%
“…Given such biases, heterogeneous reports are expected, and data must be interpreted with caution. For instance, in Manitoba, some reports suggest that addiction rates may be lower among French-speaking OLMC adults (although sometimes only marginally) compared with this province’s English-speaking majority (Chartier 28 ; Chartier et al, 29 ), while broader substance use may be greater among OLMC postsecondary student populations compared with their majority language peers (Gueye et al, 30,31 ). Others report substance-specific differences, with binge drinking being more prevalent among Anglophone (majority) and cannabis use more common among Francophone (OLMC) postsecondary students in this province 32 .…”
Section: Results and Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation